Manajemen Dan Eksekutif - Burhanudin Gesi; Rahmat Laan; Fauziyah Lamaya (Jurnal Manajemen, 2019)
In the business world the use of management is still relatively new.The economic literature of the 19th and 20th centuries is stillunknown to him. The writers at that time, used the terms owner,businessman or capitalist to express those who ran commercial,trade or factory businesses. Modern humans could be said to behuman beings who endeavored without being alone, but ratherthrough them through joint ventures in organizations / companies.Here there are individual relationships with organizations /companies that are reciprocal with a high level of interdependenceand interaction. These interdependencies and interactions areplayed in the role and role of a very important 'leader'. In essence,the dynamics of organizational / corporate life require properbehavior from employees in the sense of encouraging, and fosteringa willingness to bring personal interests to broader interests,namely business interests in the company as a whole in the controlof someone professional manager (ecsseccutivelly professionalleader).